Singapore's battle against hepatitis B in the late twentieth century - Chionh, Lynn (Nanyang Technological University, 2023)
In the late twentieth century, hepatitis B was viewed as a shameful cultural disease due to its longstanding association with backwardness. Current literature that espouse the above often see the disease in a vacuum. Hepatitis B, much like other infectious diseases, must be understood in the social and political context of the time to determine the extent of its stigmatization. This thesis challenges the popular discourse of hepatitis B as a stigmatizing disease. It argues that Singapore’s social and political context of having exponential tourism even at the height of hepatitis B and its multicultural background resulted in hepatitis B not being deemed as a disgraceful disease in Singapore. Hence, the government did not provide free immunization and did not carry out extensive public health education and policing of public social practices, healthcare facilities and other hepatitis B hotspots. This exemplifies how the cultural construct of illnesses is dependent on the social and political context of the time which caused the responsibility of managing hepatitis B to fall onto the public and the owners of such establishments. Hence, they had to step up to police themselves to guard themselves against hepatitis B.